Vinegar production from pickled mango peel waste - Mongkontanawat, N.; Prapaiwong, T. (International Journal of Agricultural Technology, 2024)
The pickled mango industry was found to reduce waste by fermenting pickled mango peel into vinegar. The results revealed that a 1:4 ratio of mango pickle peel to water resulted in the highest ethyl alcohol content production, with a significant difference (p≤ 0.05). Moreover, a 15 % (v/v) acetic acid culture showed significantly (p≤ 0.05) high acetic acid content. The produced pickled mango peel vinegar was then subjected to sensory evaluation and compared with commercial apple cider vinegar. Interestingly, the produced vinegar exhibited significantly (p≤ 0.05) higher aroma, taste, and overall acceptability compared to the commercial vinegar, although there were not significant differences in color and texture. Overall, this study represents a novel approach to vinegar production from pickled mango waste, contributing to waste reduction and environmental sustainability